BudayaTadarus Yang Terus Tergerus di Keumukiman Lam Ara - Kota Banda Aceh - Riswan (Kodepena Indonesia, 2022)
Tadarus adalah suatu kegiatan membacaAL Quran pada malam-malambulan Ramadhan/puasa yang dilakukan oleh sekelompokanak-anakmuda yang masihremajahingga yang sudahdewasabahkan juga terkadangoleh bapak-bapakyang dilakukan pada tiap-tiapMeunasah (Musalla) pada tiapdesa/Gampong di kota Banda Aceh selamasatubulanpenuh, kegiataninitelahmembudayaselamabertahun-tahun yang dimulaidarisetelahselesaishalat Tarawih pada malampertamahingga padamalamakhitbulan Ramadhan/puasa. BudayakegiatanTadarusinitelahdimulaisejak lama secaraturuntemurunsehinggatidakdiketahuidalamsejarahkapanbudayainidimulai. Maksud dan tujuandarikegiataniniadalahsemata-matauntukmenghidupkanmalam-malamBulanRamadhan dan juga sebagaiwadahtempatbersilahturahmibagisesamamasyarakatdesaterutamakalau yang barujadipendudukDesa/Gampong yang barudatangbaikitudisebabkan oleh perkawinanataupunperpindahanpenduduk.Peserta yang mengikutiTadarusiniberkisarantara 5 sampaidengan 10 orang secaraberganti-gantian dan tidakmemilikiikatanapapun dan tidakmempunyaiketuakelompoknya. Merakamembaca Qur’an secaraikhlas dan kesadaran masing-masing peserta. Kegiataninisecaraotomatistimbul pada saatbulan Ramadhan dan denganresmidibuka pada malampertama Ramadhan setelahshalat Tarawih dan juga akanditutup pada malampembagian zakat fitrah di malamakhirbulam Ramadhan oleh Tengku/Imam ChikGampong KegiatanTadarusinidiselingidenganberbagaimacamkue-kuebasah yang dibuat oleh para pendudukdesa dan diantarkeMeunasahanatara 7 – 10 kepalakeluargasetiapmalamnyasecarabergantian, sehingga para pesertaTadarusdapatmelakukankegaiatanmembaca Al Qur’an hinggatibanyawaktuMakanSahur. Tadarus is an activity of reading the Quran on the nights of the month of Ramadan/fasting carried out by a group of young people from teenagers to adults and sometimes even by fathers which is carried out in each Meunasah (Musalla) in each village. /Gampong in the city of Banda Aceh for one full month, this activity has been entrenched for years starting from after the Tarawih prayer on the first night until the last night of the month of Ramadan/fasting. The culture of this Tadarus activity has been started for a long time from generation to generation so it is not known in history when this culture began. The purpose and objective of this activity is solely to liven up the nights of the Month of Ramadan and also as a place to stay in touch for fellow villagers, especially if new residents of the Village/Gampong have just arrived, whether due to marriage or migration. Participants who take part in this Tadarus range from 5 to 10 people alternately and do not have any ties and do not have a group leader. They read the Qur'an sincerely and the awareness of each participant. This activity automatically arises during the month of Ramadan and is officially opened on the first night of Ramadan after Tarawih prayers and will also be closed on the night of the distribution of zakat fitrah at the end of the month of Ramadan by Tengku/Imam ChikGampong This Tadarus activity is interspersed with various kinds of wet cakes made by the villagers and delivered to the Meunasah between 7-10 families each night in turn, so that the Tadarus participants can carry out activities of reading the Qur'an until it is time to eat Sahur.